The Behavioral Inhibition System, Behavioral Activation System, and Experiential Avoidance as Explanatory Variables of Comorbid Chronic Pain and Posttraumatic Stress Symptoms. - Serrano-Ibáñez, Elena Rocío; Ramírez-Maestre, María del Carmen; Esteve-Zarazaga, Rosa; López-Martínez, Alicia Eva (Taylor & Francis, 2019)
Background: The variables that underlie comorbid chronic pain and posttraumatic stress symptoms (PTSS) are not yet clearly established. Objective: The aim of the present study was to analyse the role of the behavioural inhibition system (BIS), behavioural approach system (BAS) and experiential avoidance (EA) in pain adjustment (i.e. pain intensity, daily functioning and pain-related impairment) in patients with chronic pain and PTSS. Methods: A battery of instruments was administered to 388 chronic pain patients. The sample was divided into those with PTSS (n = 194) and those without PTSS (n =194). Results: Significant differences were found between groups in the BIS, EA, impairment and daily functioning. No differences were found between groups in the BAS. Structural equation modelling showed that the BIS and EA were associated with worse adjustment in the 194 patients with both chronic pain and PTSS. The BAS was associated with a lower level of pain and greater daily functioning. Conclusion: The findings provide evidence that BIS and BAS activation and EA play a role in adjustment to chronic pain in patients with concurrent PTSS. These results may help guide the development of psychological treatments for patients with both conditions
https://openpolicyfinder.jisc.ac.uk/id/publication/18644
Keywords: Dolor crónico - Aspectos psicológicos; Conducta; Evitación (Psicología); Chronic pain; Posttraumatic stress symptoms; Behavioural inhibition system; behavioural approach system; Experiential avoidance; Pain adjustment